Production and characterisation of analogues of the antimicrobial tyrocidine peptides with modified aromatic amino acid residues - Berge, Simon Nicholas (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.